2017
DOI: 10.5433/1679-0359.2017v38n4p2041
|View full text |Cite
|
Sign up to set email alerts
|

Fiber composition and degradability of cold season green forage and pre-dried silage harvested at pre-flowering

Abstract: This study aimed to evaluate the contents of hemicellulose, cellulose, and lignin, as well as the rates of dry matter degradability in forage and pre-dried silage of different winter cereals harvested at preflowering. The experiment was conducted by the Animal Production Center (NUPRAN), Department of Agricultural and Environmental Sciences, State University of Midwest (UNICENTRO). It is located in Guarapuava -PR, Brazil. The study was part of the Master's Degree in Crop Production. As experimental materials, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 9 publications
1
13
1
Order By: Relevance
“…The lower concentration of total soluble nutrients in the second cut in both stands may be related to the higher proportion of stems in this cut. Horst et al (2017) in studies with black oats for the production of pre-dried with 265 plants m 2 found mean values of total soluble nutrients of 28.12%, which is lower than that of the present study.…”
Section: Still Incontrasting
confidence: 89%
See 1 more Smart Citation
“…The lower concentration of total soluble nutrients in the second cut in both stands may be related to the higher proportion of stems in this cut. Horst et al (2017) in studies with black oats for the production of pre-dried with 265 plants m 2 found mean values of total soluble nutrients of 28.12%, which is lower than that of the present study.…”
Section: Still Incontrasting
confidence: 89%
“…This can be explained by the high correlation between acid detergent fiber and dry matter digestibility (Van soest, 1994). Horst et al (2017) evaluated cultivars of different winter cereals for pre-dried production, using 265 plants m 2 , for black oat cv. EMB 139, and found mean values of 60.9%, 23.7%, 42.3% and 5.7% for in situ dry matter digestibility and hemicellulose, cellulose and lignin contents, respectively.…”
Section: Still Inmentioning
confidence: 99%
“…The white oat and both barleys, as forages, showed the highest contents of crude protein, probably due to the greater proportion of leaves in their composition. According to Horst et al (2017), a high concentration of leaves implies a greater concentration of digestible nutrients in the dry matter. Carvalho and Pires (2008) reported that greater changes in the physical composition of forage plants occur due to maturity, where there is a downward trend in the nutritive value with the advance of the cycle because of the lignification of the cell wall and the reduction in participation of leaves in relation to stems.…”
Section: Resultsmentioning
confidence: 99%
“…Pre-drying provides direct effects on forage carbohydrate content, varying particularly with initial moisture content (Horst et al, 2017). When assessing the silage fiber composition of different winter cereals, Meinerz et al (2011b) they reported higher values of hemicellulose (348 g kg -1 ).…”
Section: Resultsmentioning
confidence: 97%